An Enhanced Model for Prediction of Young Modulus of Composite - Gupta, Ritu; Norrozila, Sulaiman; Beg, M. D. H.; Gupta, Arun (Elsevier Ltd, 2012)
This paper presents computer simulation model for prediction of young modulus for Wood Plastic Composite (WPC) properties. The effect on modulus of natural fibers which affect the strength and stiffness of the composites were studied. The results show that the percentage of void volume inside the fibers is reduced using the proposed model. The results are validated with the experimental data and it was shown that the results from simulations model are closed to the experimental result.